A virtual reality environment to study work-related objectification - Giulio Puzella; Antonio Sterlicchio; Cristina Baldissarri; Anna Manfredi; Tobias Greitemeyer; Alessandro Gabbiadini (Acta Psychologica)
The present work introduces the ACME VR paradigm, a novel virtual reality-based approach for investigating work-related objectification. Traditional laboratory methods often lack ecological validity. Therefore, VR has been used for creating a realistic paradigm maintaining high experimental control. Two scenarios were designed: an assembly line task, characterized by repetitiveness, external control, and fragmentation, and a woodworking task, adopted as a control scenario, emphasizing autonomy and holistic engagement.The effectiveness of the VR paradigm was assessed by examining a specific manifestation of objectification: self-objectification. A preliminary study assessed usability levels and interaction quality and explored the paradigm's ability to elicit self-objectification. Results demonstrated that the designed scenarios did not present interaction issues, and both user experience and overall usability were satisfactory. Moreover, the objectifying scenario induced significantly higher self-objectification and perceptions of objectifying activity than the non-objectifying scenario. These findings were further validated in the main study, where the objectifying scenario elicited higher self-objectification in terms of self-perception as instruments-like and reduced self-attribution of human mental states, confirming the impact of task characteristics on these outcomes.The paradigm's design ensures high ecological validity while maintaining rigorous experimental control. VR-specific measures, such as sense of presence and embodiment, were consistent across scenarios, validating the reliability of the simulations. This research highlights VR's potential to replicate complex workplace dynamics and manipulate key variables. It also provides researchers with an innovative, reliable, and validated tool for experimental studies to deepen the understanding of psychological mechanisms related to objectification in the workplace.